Campus by the Sea: Adapting the Landscape to Evolving Salinity - Elhusseini, Rami; Battikha, George (Universitas Diponegoro, 2022)
A lush green campus has been the American University of Beirut (AUB) flagship for the last five decades. The present decade however, saw the water well bear the brunt of growing population, decreased rainfall, and unsustainable consumption[1]. The bliss of the neighboring sea turned into a curse, as the aquifers fell short, and the extraction overload left the water table brackish and polluted. To mitigate the recently increased salinity, we combined the responsible consumption goal with the experiential education, and the innovative use of infrastructure. Water use awareness drove this effort. Luckily, the water network availed (regarding the plan to segregate the brackish network from the main waterlines). Same for the health system (streamlined vaccination program[2]) and the educational facility (greenhouse/nursery labs) both of which were intrinsic to this collaboration. Returning the greenery without spending too much green!Keyword: Innovation in adaptation, SDGs in education, Salinity tolerance, Greenery in brackish settings, Green Metrics Campus